2007
DOI: 10.31671/dogus.2019.229
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Daily and Sessional Returns of the ISE - 100 Index with Neural Network Models

Abstract: Especially for the last decade, the neural network models have been applied to solve financial problems like portfolio construction and stock market forecasting. Among the alternative neural network models, the multilayer perceptron models are expected to be effective and widely applied in financial forecasting. This study examines the forecasting power multilayer perceptron models for daily and sessional returns of ISE-100 index. The findings imply that the multilayer perceptron models presented promising per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 33 publications
0
9
0
3
Order By: Relevance
“…These studies used various types of ANN to predict accurately the stock price return and the direction of its movement. ANN has been demonstrated to provide promising results in predict the stock price return (Avci, 2007;Egeli, Ozturan, & Badur, 2003;Karaatli, Gungor, Demir, & Kalayci, 2005;Kimoto, Asakawa, Yoda, & Takeoka, 1990;Olson & Mossman, 2003;White, 1988;Yoon & Swales, 1991).. Leung et al (2000) examined various prediction models based on multivariate classification techniques and compared them with a number of parametric and nonparametric models which forecast the direction of the index return. Empirical experimentation suggested that the classification models (discriminant analysis, logit, probit and probabilistic neural network) outperform the level estimation models (adaptive exponential smoothing, vector auto regression with Kalman filter updating, multivariate transfer function and multilayered feed forward neural network) in terms of predicting the direction of the stock market movement and maximizing returns from investment trading.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 97%
“…These studies used various types of ANN to predict accurately the stock price return and the direction of its movement. ANN has been demonstrated to provide promising results in predict the stock price return (Avci, 2007;Egeli, Ozturan, & Badur, 2003;Karaatli, Gungor, Demir, & Kalayci, 2005;Kimoto, Asakawa, Yoda, & Takeoka, 1990;Olson & Mossman, 2003;White, 1988;Yoon & Swales, 1991).. Leung et al (2000) examined various prediction models based on multivariate classification techniques and compared them with a number of parametric and nonparametric models which forecast the direction of the index return. Empirical experimentation suggested that the classification models (discriminant analysis, logit, probit and probabilistic neural network) outperform the level estimation models (adaptive exponential smoothing, vector auto regression with Kalman filter updating, multivariate transfer function and multilayered feed forward neural network) in terms of predicting the direction of the stock market movement and maximizing returns from investment trading.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 97%
“…Tsanga et al (2007) technical indicators with ANN was utilised to created trading alert system and their findings showed that ANN can effectively guide investors when to buy or sell stocks. Avci (2007) also used technical indicators with ANN, and his finding demonstrated that ANN could be used effectively to forecast daily and sessional returns of the Ise-100 Index.…”
Section: Related Workmentioning
confidence: 99%
“…Örneğin Diler (2003), BIST-100 endeksinin bir sonraki günkü yönünü YSA kullanarak %60,81 doğruluk oranı ile tahmin etmiştir [21]. Avcı (2007) da çalışmasında BIST-100 endeksinin seanslık ve günlük getirilerini YSA ile tahmin etmiştir. Çalışma sonucunda seanslık tahminin daha başarılı sonuç ürettiğini belirtmiştir [22].…”
Section: Introductionunclassified